Peningkatan Kesiapan Keluarga dalam menghadapi Kegawatdaruratan Persalinan di Rumah melalui Edukasi dan Penanganan Awal - Sukmawati Sulfakar; Hasmidar Hasmidar; Al Munawarah Fattah; Reli Sipata (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Obstetric emergencies are one of the main causes of high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia. Many obstetric emergencies occur at home before the mother reaches a healthcare facility. Objective: To improve family preparedness in dealing with obstetric emergencies through education and initial handling training at home. Methods: The program began with a pre-test to assess the family’s initial knowledge. After measuring baseline knowledge, the main session included counseling/education, practical skill demonstrations, simulations, and participant practice. At the end of the session, a post-test was conducted to assess improvements in family knowledge. Results: The community service activity was attended by 25 participants. Based on pre-test and post-test results, there was an average knowledge increase of 45%. Participants reported that the most useful topics were hemorrhage management and referral pathways. The simulation sessions were highly interactive, and several participants were able to perform initial emergency steps independently. Health cadres also expressed readiness to provide support for pregnant women in their areas. Conclusion: This community service program successfully improved family knowledge and skills in handling obstetric emergencies at home. Education and simulations proved effective in enhancing rapid family response, thereby minimizing the risk of delayed treatment.